(untitled) (Journal of Partial Differential Equations, 1994)
The present paper is concerned with the global C&sup2-estimates of solutions to boundary value problems for degenerate elliptic. Monge-Ampere equations. Both of degeneracies of the boundary data and the right hand side of the equation are considered. In two dimensional case a result about smooth solutions is also contained.